Diagnostic accuracy of BP180 NC16a and BP230‐C3 ELISA in serum and saliva of patients with bullous pemphigoid. (1st April 2015) - Esmaili, N.; Mortazavi, H.; Kamyab‐Hesari, K.; Aghazadeh, N.; Daneshpazhooh, M.; Khani, S.; Chams‐Davatchi, C.
Summary: Background: Bullous pemphigoid (BP) is a subepidermal blistering disease, characterized by autoantibodies directed against BP180 and BP230. Collecting saliva is an easy and painless way of obtaining biological samples, and can be used for diagnosis of autoimmune diseases. Aim: To compare the diagnostic accuracy of serum and salivary BP180‐NC16a and BP230‐C3 in the initial diagnosis of BP. Methods: We assessed 50 patients newly diagnosed with BP and 50 healthy controls. The diagnosis of BP was confirmed based on clinical, histopathological and immunofluorescence findings. Serum and saliva samples were collected from both groups, and BP180 and BP230 titres were assessed using commercially available ELISA kits. Results: Using serum, the sensitivity of the serum BP180 and BP230 ELISA assays was 88% and 48%, respectively, and the specificity of both was 96%. Using saliva with the cutoff value proposed by the manufacturer, sensitivity was 56.2% and 14.6%, and specificity was 98% and 100%, respectively. Using the best calculated cutoff for saliva, sensitivity increased to 87.5% and 77.1%, and specificity to 96% and 62%, respectively. There was a significant correlation between serum and saliva BP180 levels and the severity of skin disease. Both serum and saliva BP230 levels were significantly higher in patients with mucosal involvement. Conclusion: Serum BP180 NC16a ELISA is a sensitive and specific test for the initial diagnosis of BP, whereas serum BP230‐C3 ELISA is highly specific, but less sensitive. Saliva may be a noninvasive and convenient alternative for use in the BP180 NC16a ELISA to diagnose BP.